EDITORIAL - ALAM, AHM Zahirul (IIUM Engineering Journal, 2020)
CHIEF EDITOR Ahmad Faris Ismail, IIUM, Malaysia TECHNICAL EDITOR Sany Izan Ihsan, IIUM, Malaysia EXECUTIVE EDITOR AHM Zahirul Alam, IIUM, Malaysia ASSOCIATE EDITOR Nor Farahidah Za’bah, IIUM, Malaysia LANGUAGE EDITOR Lynn Mason, Malaysia COPY EDITOR Hamzah Mohd. Salleh, IIUM, Malaysia EDITORIAL BOARD MEMBERS Abdullah Al-Mamun, IIUM, Malaysia Abdumalik Rakhimov, IIUM, Malaysia Ali Sophian, IIUM, Malaysia Erwin Sulaeman, IIUM, Malaysia Hanafy Omar, Saudi Arabia Hazleen Anuar, IIUM, Malaysia Konstantin Khanin, University of Toronto, Canada Ma'an Al-Khatib, IIUM, Malaysia Md Zahangir Alam, IIUM, Malaysia Meftah Hrairi, IIUM, Malaysia Mohamed B. Trabia, United States Mohammad S. Alam, Texas A&M University-Kingsville, United States Mustafizur Rahman, National University Singapore, Singapore Ossama Abdulkhalik, Michigan Technological University, United States Othman O Khalifa, IIUM, Malaysia Razi Nalim, IUPUI, Indianapolis, Indiana, United States Rosminazuin AB. Rahim, IIUM, Malaysia Waqar Asrar, IIUM, Malaysia INTERNATIONAL ADVISORY COMMITTEE Anwar, United States Abdul Latif Bin Ahmad, Malaysia Farzad Ismail, USM, Pulau Pinang, Malaysia Hanafy Omar, Saudi Arabia Hany Ammar, United States Idris Mohammed Bugaje, Nigeria K.B. Ramachandran, India Kunzu Abdella, Canada Luis Le Moyne, ISAT, University of Burgundy, France M Mujtaba, United Kingdom Mohamed AI-Rubei, Ireland Mohamed B Trabia, United States Syed Kamrul Islam, United States Tibor Czigany, Budapest University of Technology and Economics, Hungary Yiu-Wing Mai, The University of Sydney, Australia. AIMS & SCOPE OF IIUM ENGINEERING JOURNAL The IIUM Engineering Journal, published biannually (January and July), is a carefully refereed international publication of International Islamic University Malaysia (IIUM). Contributions of high technical merit within the span of engineering disciplines; covering the main areas of engineering: Electrical and Computer Engineering; Mechanical and Manufacturing Engineering; Automation and Mechatronics Engineering; Material and Chemical Engineering; Environmental and Civil Engineering; Biotechnology and Bioengineering; Engineering Mathematics and Physics; and Computer Science and Information Technology are considered for publication in this journal. Contributions from other areas of Engineering and Applied Science are also welcomed. The IIUM Engineering Journal publishes contributions under Regular papers and Invited review papers. It also welcomes contributions that address solutions to the specific challenges of the developing world, and address science and technology issues from an Islamic and multidisciplinary perspective. REFEREES’ NETWORK All papers submitted to IIUM Engineering Journal will be subjected to a rigorous reviewing process through a worldwide network of specialized and competent referees. Each accepted paper should have at least two positive referees’ assessments. SUBMISSION OF A MANUSCRIPT A manuscript should be submitted online to the IIUM-Engineering Journal website at http://journals.iium.edu.my/ejournal. Further correspondence on the status of the paper could be done through the journal website. Whilst every effort is made by the publisher and editorial board to see that no inaccurate or misleading data, opinion or statement appears in this Journal, they wish to make it clear that the data and opinions appearing in the articles and advertisement herein are the responsibility of the contributor or advertiser concerned. Accordingly, the publisher and the editorial committee accept no liability whatsoever for the consequence of any such inaccurate or misleading data, opinion or statement. IIUM Engineering Journal ISSN: 1511-788X E-ISSN: 2289-7860 Published by: IIUM Press, International Islamic University Malaysia Jalan Gombak, 53100 Kuala Lumpur, Malaysia Phone (+603) 6421-5014, Fax: (+603) 6421-6298